2020
DOI: 10.5194/acp-20-4889-2020
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and molecular compositions of water-soluble and water-insoluble brown carbon (BrC) aerosols in northwest China

Abstract: Abstract. Brown carbon (BrC) contributes significantly to aerosol light absorption and thus can affect the Earth's radiation balance and atmospheric photochemical processes. In this study, we examined the light absorption properties and molecular compositions of water-soluble (WS-BrC) and water-insoluble (WI-BrC) BrC in PM2.5 collected from a rural site in the Guanzhong Basin – a highly polluted region in northwest China. Both WS-BrC and WI-BrC showed elevated light absorption coefficients (Abs) in winter (4–7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 77 publications
7
31
4
Order By: Relevance
“…In this study, 1,4-phenanthraquinone was used to conduct a positive control, of which the DTT consumption rate was 0.46 ± 0.03 µM DTT/min (n = 10). The rate was similar to those reported in the previous studies (Fan et al, 2018;Lin and Yu, 2019). Finally, principal component analysis (PCA) was performed to investigate the key factors that may affect the DTT activities from a series of characteristics of the BrC fraction.…”
Section: Oxidative Potentialsupporting
confidence: 79%
“…In this study, 1,4-phenanthraquinone was used to conduct a positive control, of which the DTT consumption rate was 0.46 ± 0.03 µM DTT/min (n = 10). The rate was similar to those reported in the previous studies (Fan et al, 2018;Lin and Yu, 2019). Finally, principal component analysis (PCA) was performed to investigate the key factors that may affect the DTT activities from a series of characteristics of the BrC fraction.…”
Section: Oxidative Potentialsupporting
confidence: 79%
“…Their optical properties could be modified following photochemical processing with both photobleaching (the loss of light absorptivity) and photo enhancement possibly occurring. [77,79] The formation and degra dation of BrC by photochemical processes may complicate the understanding of atmospheric BrC. [79] A series of researches has focused on changes in light absorptivity and oxidation state of BrC under illumination and O 3 and •OH radicals (abundant during the daytime).…”
Section: Brown Carbonmentioning
confidence: 99%
“…[77,79] The formation and degra dation of BrC by photochemical processes may complicate the understanding of atmospheric BrC. [79] A series of researches has focused on changes in light absorptivity and oxidation state of BrC under illumination and O 3 and •OH radicals (abundant during the daytime). Dasari et al [35] found that atmospheric photooxidation reduced the light absorptivity (i.e., photobleaching) of WSBrC by ≈84% during longrange transport over the altitude of 6000 km in the IndoGangetic Plain, with a firstorder bleaching rate of 0.20 ± 0.05 per day during overocean travel to an Indian Ocean receptor site across Bay of Bengal.…”
Section: Brown Carbonmentioning
confidence: 99%
“…Detailed information of the sampling campaign was described by J. Li et al (2020). Briefly, daytime (08:00-20:00) and nighttime (20:00-08:00 next morning) PM 2.5 samples were collected on pre-combusted (450°C for 6 h) quartz filters (Whatman QM/A) using a high-volume air sampler (TISCH, TE6070DV-BL, 1.13 m 3 •min −1 ) during August 3-23, 2016 (summer, 42 samples) and January 20-February.…”
Section: Pm 25 Sample Collectionmentioning
confidence: 99%
“…The details for the sample extraction procedures and chemical analysis were provided in previous publications (J. Li et al, 2014Li et al, , 2020Steven et al, 2016;T. Zhang et al, 2011).…”
Section: Kappa and Zsr Calculationmentioning
confidence: 99%